Diversidade da produç\~ao nos estabelecimentos da agricultura familiar no Brasil: Uma análise econométrica baseada no cadastro da Declaraç\~ao de Aptid\~ao ao Pronaf (DAP) - Regina Helena Rosa Sambuichi; Ernesto Pereira Galindo; Rodrigo Mendes Pereira; Michel Constantino; Matheus dos Santos Rabetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– This paper analyzes the production diversity among Brazilian agricultural family farms, using the DAP (declaration of Pronaf entitlement). The diversity is measured with a Simpson index, that goes from zero, for monocultures, to one. Production is considerably diversified in these types of farms. 57% of them have a diversification index above 0,35, although it has been noticed an increase in specialization in recent years. The share of monoculture farms rose from 25% in 2012 to 33% in 2014. The diversification index is set as the dependent variable on a Tobit regression with variables that are commonly used to explain the decision to diversify, such as regional dummies, farm size, number of farms, farmer's age, income from social benefits, education, gross production, or a dummy for access to technical assistance. All of these variables have significant effects on production diversity. The results suggest a strong regional bias in terms of diversification, as well as the importance of technical assistance and the availability of technologies in order to spur diversification among family farmers.
Keywords: H24; N46; E62; 330; diversification; public policies; sustainability; family farms